Caracterização e purificação parcial de substância antagonista produzida por Bacteroides fragilis isolado de paciente com infecção intra-abdominal - Marcela Nascimento Pinheiro Braga (2016)
The indigenous microbiota is extremely rich and diverse, in special the intestinal microbiota. Among its members Bacteroides and Parabacteroides should be highlighted. These bacteria are Gram negative, obligate anaerobes, associated with the etiopathogenesis of relevant infectious diseases such as, intra-abdominal infections. Bacteroides and Parabacteroides express the ability to synthesize bacteriocins, proteinaceous substances that play an ecological function, particularly in densely colonized habitats such as the intestine, confering a competitive advantage to the producer strains. This study aimed to evaluate the expression of bacteriocin-like substances by 40 isolates of Bacteroides and Parabacteroides recovered from patients with intra-abdominal infections. We searched for antagonism expression by employing the overlay method, using, as indicator, in addition to the test strains, 42 reference strains of Gram negative and Gram positive bacteria. After screening for antagonistic activity one producer strain was selected and employed in the subsequent steps of the study. This isolate (Bacteroides fragilis) was submitted to extraction, purification, and partial characterization of the antagonistic substance. Bacteroides ovatus and Bacteroides caccae were selected as indicator strains. The intracellular extracts precipitated with (NH4)2SO4 at concentrations of 30% (C30) and 50% (C50) showed activity. This extracts C30 and C50 were inactivated by proteases and high temperatures, and remained active after exposure to organic solvents and a wide range of pH. Both active fractions expressed antagonistic activity of bacteriostatic nature. The extract C50 was submitted to ion exchange chromatography, gel filtration chromatography and reversed phase chromatography, following this order. The fraction 2C remained active. Mass spectrometry of fraction 2C presented ions of approximately 1300 Da, which generated a more intense signal. A search for similarity between sequenced fragments and proteins described in the databases BLASTP and Antimicrobial Peptide Database was conducted. The sequence of a fragment obtained from reverse phase chromatography resulted in 100% identity with a type VII secretion protein (BLASTP). Taken together, the results indicate the production of antagonistic substances by the B. fragilis isolate under study. It is plausible to assume that they play a relevant role in interbacterial relationships as a virulence factor especially in a such complex environment as we observe in an event of an intra-abdominal infection.